Fonetično-fonološka analiza govora na primeru otroške radijske igre - Maver, Manica (Jezik in slovstvo, 2019)
The main part of the article presents an analysis of a short extract of a recorded radio drama for children. The introduction points out that the genre of radio drama is neglected by academic and critical circles, probably due to the lack of specific scholarly tools for its analysis and evaluation. The article then illustrates all of the sound elements that help create audio drama: voices, speech, music, sound effects and silence. Finally, a concrete example of speech analysis in radio drama is presented: the example chosen is an extract from the children's play Bogdanova zmaga (Bogdan's Victory) produced by Radijski oder (Radio Stage) for Radio Trst A (a Slovenian radio station in Trieste). The analysis attempts to present a tool for a more scientific and objective study of this artform.
Keywords: analiza govora; fonetične analize; fonološke analize; Lombar, Lojzka: Bogdanova zmaga; otroške radijske igre; slovenska književnost; zvočna izrazila